Switch phenomenon in bipolar disorders: What is it? - Anand Bhogaraju (Telangana Journal of Psychiatry, 2016)
The phenomenon of Affective switch process is not well understood. It is difficult to differentiate switch from natural course of emergence of Manic/Hypomanic episodes. International Society of Bipolar Disorders (ISBD) has worked out operational definition for switch. Bipolar disorder I has highest rates of switch compared to Bipolar Disorders II. Tricyclics and Tetracyclic Antidepressants and Venlafaxine have highest switch rates. Controversy exists on role of mood stabilizers protecting from switch. Switch to depression is seen in some studies but meta-analyses have not focused on this issue. Among the correlates in prediction of switch, history of a positive family history of a mood disorder, symptoms of sub threshold mania, emotional dysregulation, behavior problems, Psychotic symptoms, suicide attempt and high scores on the aggressive-disruptive behavior item of the Young Mania Rating Scale appear promising. Mechanisms of switch are yet to be understood. Cautious prescribing of antidepressants for brief periods has been suggested in Pediatric Mood disruptions.